2015
DOI: 10.1096/fj.15-276394
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of preparing the monoform structure of catalytic antibody light chain

Abstract: Along with the development of antibody drugs and catalytic antibodies, the structural diversity (heterogeneity) of antibodies has been given attention. For >20 yr, detailed studies on the subject have not been conducted, because the phenomenon presents many difficult and complex problems. Structural diversity provides some (or many) isoforms of an antibody distinguished by different charges, different molecular sizes, and modifications of amino acid residues. For practical use, the antibody and the subunits mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…After ultrasonication of the E coli , a soluble fraction was recovered and applied to Ni‐ion affinity chromatography, as described in Section . After this step, Cu(II) ion was added to make the heterogeneous structures of the light chain (possessing different electrical charges) to the homogeneous (a single charge), which contributes to the efficient production and the high reproducibility (see Reference ). Then, the treatment of EDTA (for taking out Cu from the system) was carried out to keep the stability of the homogeneous structure for a long‐term period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After ultrasonication of the E coli , a soluble fraction was recovered and applied to Ni‐ion affinity chromatography, as described in Section . After this step, Cu(II) ion was added to make the heterogeneous structures of the light chain (possessing different electrical charges) to the homogeneous (a single charge), which contributes to the efficient production and the high reproducibility (see Reference ). Then, the treatment of EDTA (for taking out Cu from the system) was carried out to keep the stability of the homogeneous structure for a long‐term period.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one has to be aware of the structural diversity problem of antibodies. We were able to solve the structural diversity issue, and reported how to control for an antibody having a mono‐form structure . With this technology, we can make the catalytic antibody structure take a monomolecular form, which is necessary to preparing the same conformational antibody to attain effective production well as reproducible reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Using the FRET-A (26)(27)(28)(29)(30)(31)(32)(33) [MCA-SNKGAIIGK(DNP)rrr-NH 2 ] substrate, we examined catalytic activity by T99wt and T99-Pro95(−) at a temperature of 37°C. The reaction time courses are shown in Fig.…”
Section: Cleavage For Fret-amentioning
confidence: 99%
“…Regarding the amount of Cu 2+ incorporated in the CL, the chemical analysis implies that a ratio of 0.6 eq Cu 2+ to CL was the maximum, suggesting that two CL molecules bind with one Cu 2+ . The binding site of Cu 2+ may be close to the C terminus where His195 and Cys220 are located, as suggested by our previous study on the full length of the human antibody light chains (25). In the constant region of antibody light chain, there is a zinc finger-like motif, which can bind with a divalent metal ion.…”
Section: Discussionmentioning
confidence: 83%
“…We have also reported that molecular heterogeneity is caused by different electrical charges and different molecular sizes in a mouse monoclonal antibody (24). In addition, we recently found similar molecular heterogeneity in recombinant human catalytic antibody light chains (25). An antibody light chain consists of 2 domains: the variable region of light chain and the constant region of the light chain [i.e., the catalytic antibody k light chain (CL)].…”
mentioning
confidence: 99%